AB0564 Starting Dose of Prednisolone for Japanese Patients with Polymyalgia Rheumatica. (10th June 2014) - Aoki, A.; Oka, H.; Nakamura, M.; Aoki, I.
Abstract : Background: Polymyalgia rheumatica (PMR) is a common inflammatory condition of elderly persons. Clinical symptoms respond to low-dose glucocorticoids, but treatment is often required for several years. The recent UK guidelines and a systematic review reported that an adequate starting dose of prednisolone (PSL) for PMR patients is 15 mg daily 1, 2 . However, the majority of PMR patients in Japan have shorter heights and lower weights than patients in Western countries. Therefore, this starting dose of PSL, when calculated as mg/kg body weight (PSL/BW), might be too high for Japanese patients who generally have a slighter build. Objectives: We evaluated the starting doses of PSL and the clinical courses of Japanese PMR patients. Methods: This was a retrospective study in a single hospital. We studied 14 patients with a diagnosis of PMR according to the modified Bird's criteria 3 (positive for C reactive protein (CRP) instead of erythrocyte sedimentation rate (ESR) >40mm/1 hour, who were followed-up for more than 6 months. Patients who had one or more of the following symptoms were excluded: recent temporal or occipital pain, a tender and/or swollen temporal artery, jaw claudication, and impairment of vision. The mean starting dose of PSL/BW of the 14 patients was 0.3 mg/kg. Thus, the patients were divided into 2 subgroups based on their starting doses of PSL/BW: less than 0.3 mg/kg (group L) and more than 0.3 mg/kg (group H). Remission was defined as the absence of symptoms for more than one month after the withdrawal of PSL. Relapse was defined by the recurrence of clinical symptoms accompanied by both serum CRP elevation and a requirement for an increase in PSL dose. Demographic and clinical data were obtained from the medical records. The statistical significance of the differences between the two groups of patients was determined by the Mann-Whitney U test and the chi-squared test. Results: The median follow-up was 17.5 months (range 8.5-24.5 months). Among the 14 patients, 9 were women. The median body weight was 44.5 kg (interquartile range 40-53 kg); eight of the 9 women and 1 of the 5 men weighed less than 50 kg. Starting doses of PSL were 10 mg in 5 patients, 15 mg in 7 patients, and 20 mg in 2 patients. Seven patients each belonged to group L and H. There was no significant difference in follow-up months, sex, age, BW, or serum CRP at diagnosis between the 2 groups. Two patients from both group L and H achieved remission. In addition, the clinical course, including the relapse and PSL withdrawal rate, were similar between the 2 groups. Conclusions: A starting dose of PSL of <0.3 mg/kg was equally as effective as that of >0.3 mg/kg. Calculating the starting PSL dose by BW might be more appropriate, especially for elderly low-BW patients in Japan, to prevent deterioration of their prognosis. References: Hemanddez-Rodriguez J, et al. Treatment of polymyalgia rheumatica: a systematic review. Arch Intern Med 2009; 169:1839-1850. Dasgupta, B, et al. BSR and BHPR guidelines for the management of polymyalgia rheumatica. Rheumatology 2010; 49:186-190 Bird H.A, Esselinckx W, J, et al. An evaluation of criteria for polymyalgia rheumatica. Ann Rheum Dis. 1979; 38: 434-439. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1157